Oxidative coupling of methane over Mn2O3-Na2WO4/SiC catalysts - Kim, Jieun; Park, La Hee; Ha, Jeong Myeong; Park, Eun Duck (Catalysts, 2019)
The oxidative coupling of methane (OCM) is operated at high temperatures and is a highly exothermic reaction; thus, hotspots form on the catalyst surface during reaction unless the produced heat is removed. It is crucial to control the heat formed because surface hotspots can degrade catalytic performance. Herein, we report the preparation of Mn2O3-Na2WO4/SiC catalysts using SiC, which has high thermal conductivity and good stability at high temperatures, and the catalyst was applied to the OCM. Two Mn2O3-Na2WO4/SiC catalysts were prepared by wet-impregnation on SiC supports having different particle sizes. For comparison, the Mn2O3-Na2WO4/SiO2catalyst was also prepared by the same method. The catalysts were analyzed by nitrogen adsorption-desorption, X-ray diffraction, scanning electron microscopy, and transmission electron microscopy. The transformation of SiC into α-cristobalite was observed for the Mn2O3-Na2WO4/SiC catalysts. Because SiC was completely converted into α-cristobalite for the nano-sized SiC-supported Mn2O3-Na2WO4 catalyst, the catalytic performance for the OCM reaction of Mn2O3-Na2WO4/n-SiC was similar to that of Mn2O3-Na2WO4/SiO2. However, only the surface layer of SiC was transformed into α-cristobalite for the micro-sized SiC (m-SiC) in Mn2O3-Na2WO4/m-SiC, resulting in a SiC@α-cristobalite core-shell structure. The Mn2O3-Na2WO4/m-SiC showed higher methane conversion and C2+ yield at 800 and 850 °C than Mn2O3-Na2WO4/SiO2.
Keywords: Mn2O3-Na2WO4/SiC; Oxidative coupling of methane; Silicon carbide; Thermal conductive material